2008
DOI: 10.1007/s00464-008-9992-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic intracorporal colorectal sutured anastomosis using the Radius Surgical System in a phantom model

Abstract: This study demonstrated the feasibility of laparoscopic colorectal anastomosis using RSS. Anastomosis with RSS was shown to be safer. The three participants evaluating ergonomy reflected less discomfort in hand/wrist using RSS. Others ergonomic problems were comparable to CLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The steerable tip enlarges the instrument's workspace and allows the surgeon to reach structures that were otherwise inaccessible before [9]. Many studies have demonstrated the feasibility and advantages of steerable devices in clinical applications [2,4,[8][9][10][11][12][13][14][15][16]. Such instruments are also beneficial for single-port laparoscopic surgery, which seeks to reduce invasiveness and trauma to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The steerable tip enlarges the instrument's workspace and allows the surgeon to reach structures that were otherwise inaccessible before [9]. Many studies have demonstrated the feasibility and advantages of steerable devices in clinical applications [2,4,[8][9][10][11][12][13][14][15][16]. Such instruments are also beneficial for single-port laparoscopic surgery, which seeks to reduce invasiveness and trauma to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Torres et al . found that 21 cases were needed to achieve a satisfactory laparoscopic anastomoses time ( 12 ). In a recent study, the learning curve of laparoscopic right hemicolectomy with overlap anastomosis was decreased gradually and stabilized after 5 cases for experienced surgeons ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frede et al state that ‘compared to our experimental experiences with conventional reconstructive laparoscopic surgery the learning curve of the [Radius] is significantly shorter’, and that even complex tasks such as complete urethro-vesical anastomoses ‘require less than 10 trials to maintain a good quality of performance’ [29]. However, when performing colorectal anastomosis in a phantom model, Torres Bermudez et al found a learning curve of 21 procedures before no reduction in completion time was observed [36]. Waseda et al acknowledge that manipulation using the Radius is significantly different from traditional manual laparoscopic instruments and that tip rotation is less intuitive than robotic systems, and therefore, suggest long practice times with the instrument [37].…”
Section: Devicesmentioning
confidence: 99%
“…The studies also noted improved ergonomics in comparison to conventional laparoscopic instruments. It has also been noted that the Radius avoids forced wrist flexion and exaggerated shoulder and elbow angles that occur with conventional instruments [36]. …”
Section: Devicesmentioning
confidence: 99%